Mobile Banking Adoption-A Segmentation Analysis - Sihotang, Ellen Theresia; Hermansyah, Deny; Laga, Sinnaring; Murdiawati, Dewi (Jurnal Mebis, 2024)
Market segmentation has an important role in determining marketing strategy and can improve marketing effectiveness specifically in mobile banking (m-banking) services. The aim of this study is to measure customer perceptions of m-banking adoption through segmentation analysis based on their behavior with the TAM construct. This study generates two segments, which are moderate and active adopters. Moderate adopters are members who already have m-banking but have not actively used it. M-banking is considered as a practical, easy-to-operate and they will adopt m-banking in the coming months. Active adopters perceive m-banking as a service which can complete banking transactions quickly and overall m-banking easy to use. M-banking is important to fulfill banking needs and will continue to adopt m-banking in the future. Moderate and Active adopters trust in the bank are positive and majority young-aged. Age has a significant relationship with both clusters, so the young aged group is the right target for m-banking marketing.